Incidental Psychotherapy Within Christian Relationships: Mental Health Benefits from Therapeutic Alliances Built on the Caring Love of Christians - Harcum, E. Rae (Hamilton Books, 2010)
Incidental Psychotherapy within Christian Relationships points out the close similarity between the loving connections of Christians and therapeutic relationships between psychotherapists and clients. Thus, a simple Christian connection has an incidental therapeutic value for a troubled friend. This book continuously emphasizes that a Christian connection is never forged for the purpose of restoring mental health, but to obey the Christian mandate to love. The Christian connection, as a therapeutic alliance, merely provides a personal preparatory stage for possible later improvement. It does not apply in any way to the use of professional therapeutic techniques. The book discusses the nature of psychotherapy, the nature of 'cures,' and the credentials of qualified psychotherapists. Chapters focus on the nature of Christian connection and ways to improve it.